Africa does not need IFRS. (1st January 2013) - Sy, Aida; Tinker, Tony
A great deal of hype surrounds the so-called revolution in accounting standard setting. The International Financial Reporting Standards (IFRS) enterprise aims to introduce a single global accounting and financial reporting language that would standardise reporting practices throughout the globe. There are several reasons why this vision may not hold, and therefore Africa should be wary. First, there are many obstacles for any US option. Second, International Financial Standards Board (IFSB) has failed to create a uniform set of standards.